The use of the NEJM knowledge + online platform to supplement traditional pulmonary didactic: a resident-led educational quality improvement project at a community hospital IM GME program - Alan Kaell; Jay Sangwan; Varvara Boryushkina; Greg Haggerty (Journal of Community Hospital Internal Medicine Perspectives, 2021)
Introduction: Many internal medicine residents struggle to prepare for both the ITE and board test. Most existing resources are simply test question banks that are not linked to existing supporting literature from which they can study. Additionally, program directors are unable to track how much time residents are spending or performing on test preparation. We looked to evaluate the benefit of using this online platform to augment our pulmonary didactics and track time and performance on the pulmonary module and ITE pulmonary section. Method: During the month-long live didactic sessions, residents had free access to the pulmonology NEJM K+ platform. A platform-generated post-test was administered with new questions covering the same key elements, including the level of confidence meta-metric. An anonymous feedback survey was collected to assess the residents’ feelings regarding using the NEJM Knowledge+ platform as compared to other prep resources. Results: 44 of 52 residents completed the pre-test. 51/52 completed the month-long didactic sessions and the post-test. Residents’ score improvement from % correct pre-test (M = 46.90, SD = 15.31) to % correct post-test (M = 76.29, SD = 18.49) correlated with levels of mastery (t = 9.60, df = 41, p < .001). The % passing improved from 1/44 (2.3%) pre-test to 35/51 (68.6%) post-test, also correlating with levels of mastery. Accurate confidence correlated with improvement from pre to post test score (r = −51, p = .001). Survey feedback was favorable.